Spain : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper contains two studies examining key issues for fiscal management and long-term fiscal sustainability in Spain. The first study discusses how best to ensure fiscal discipline at lower levels of government by examining the institutional setting and mechanisms that make this task particularly challenging in Spain's highly devolved political and fiscal system. The second study seeks to analyze the potential macroeconomic impact of different approaches to deal with the fiscal costs of aging in Spain.